The concept of neutrality in Stalin's foreign policy, 1945-1953 - Ruggenthaler, Peter, 1976- (Harvard Cold War studies book series., 2015)
"Drawing on recently declassified Soviet archival sources, this book sheds new light on how the division of Europe came about in the aftermath of World War II. The book contravenes the notion that a neutral zone of states, including Germany, could have been set up between East and West. The Soviet Union under Joseph Stalin was determined to preserve control over its own sphere of German territory. By tracing Stalin's attitude toward neutrality in international politics, the book provides important insights into the origins of the Cold War"--Provided by publisher.